Reflections on Philosophy and Scientific Reality (Docentes 2.0 Journal, 2020)
The objective of this essay was to generate some illustrative reflections of philosophical schemes of merit regarding the scientific field, being in doctoral university academic environments where currents that have become a trend are perceived, such as the poststructuralist approach, relativism, phenomenological research hermeneutics, among others. Today, the importance of philosophy with respect to humanistic existentialism in scientific contexts takes on special significance, encompassing important spaces to produce knowledge in positivist and postpositivist orientations where Gadamer's philosophical hermeneutics is framed. All of this shows an anti-scientific trend based on the manifesto of the same nature promoted by Wilhelm Dilthey. To a large extent, this responds to a necessary reflection on some philosophical trends that should serve as a criterion of scientific validity, despite the existence of an approach based on a naturalized epistemology from which it is conceived to unlink science and philosophy. In this sense, it seems pertinent to retake the necessary work of reflecting on these fundamental philosophical tendencies to achieve innovations within the planes of knowledge from doctoral university environments, but with acceptable standards linked to a high theoretical hiring as an unavoidable task. Until we understand a necessary relationship of complementarity between research with respect to philosophical currents, we will continue to accommodate processes lacking acceptable standards.
Keywords: Philosophy; Science; Reality